APPLICATION OF RESTORATIVE JUSTICE TO DRUGS CASES OF POTENT DRUG LIST G CLASS 2 - Elang Prasetyo; Taufik Makarao; Fauziah Fauziah (Fakultas Hukum, Universitas Islam As-Syafi'iyah, 2023)
The concept of Restorative Justice has actually been around for quite some time, more than twenty years ago as an alternative settlement of criminal cases, especially children, with various considerations. As stated by John Braithwaite that, Restorative Justice is a new direction between